Cavity ring-down spectroscopy of CO2 overtone bands near 830 nm. (November 2015) - Tan, Y.; Zhao, X.-Q.; Liu, A.-W.; Hu, S.-M.; Lyulin, O.M.; Tashkun, S.A.; Perevalov, V.I.
Abstract: Three bands 4003 i –00001 ( i =2, 3, 4) of the Fermi pentad of 12 C 16 O2 near 830 nm have been recorded with a continuous-wave cavity ring down spectrometer. A sensitivity at the 5×10 –11 cm −1 level allowed us to obtain line positions and intensities of these very weak bands. The measured line intensities of these three bands together with those published for the 10051–00001 and 10052–00001 bands were used to obtain the effective dipole moment parameters of 12 C 16 O2 for the Δ P =17 series of transitions, where P =2 V 1 + V 2 +3 V 3 is a polyad number ( V i ( i =1, 2, 3) are vibrational quantum numbers). Comparisons of the measured line positions and intensities of the 4003 i –00001 ( i =2, 3, 4) bands to those from the AMES and GEISA line lists are given. Highlights: Cavity ring-down spectra of 12 C 16 O2 around 830 nm were measured. Line positions and intensities of transitions were obtained for three bands. The line positions predicted by the effective Hamiltonian model agree well with the measured values.